Availability of substance abuse treatment services in Spanish: A GIS analysis of Latino communities in Los Angeles County, California - Curtis Andrew; Pan Karen B; Guerrero Erick G; Lizano Erica L (BMC, 2011)
Abstract Background The percentage of Latino clients entering outpatient substance abuse treatment (OSAT) in the United States has increased significantly in the past 10 years. Evidence suggests that a lack of services in Spanish is a significant barrier to treatment access among Latinos. Methods Using a geographic information system (GIS) approach, data from the U.S. Census Bureau and the National Survey of Substance Abuse Treatment Services (N-SSATS) were analyzed to determine the geographic distance between OSAT facilities with services in Spanish and Latino communities throughout Los Angeles County, CA. Data from N-SSATS were also analyzed using logistic regression models to examine organizational characteristics and their association with offering services in Spanish. Our GIS methods are tested in their ability to provide baseline measures to inform future analysis comparing changes in demography and service infrastructure. Results GIS analysis revealed cold spots representing high-density Latino communities with extensive travel distance to facilities offering services in Spanish. The average linear distance between Latino communities and facilities offering Spanish-language services ranged from 2 to 6 miles, while the location of the cold spots pointed to a need for services in Spanish in a particular subregion of the county. Further, secondary data analysis revealed that, on average, being privately owned (OR = .23, 95% CI = 0.06-0.90) was associated with a lower likelihood of providing services in Spanish compared to public facilities. Additionally, a facility with a state license (OR = 2.08, 95% CI = 1.12-3.88) or a higher number of Medicaid recipients (OR = 2.98, 95% CI = 1.76-5.05) was twice as likely to offer services in Spanish. Conclusion Despite the significant presence of Latinos in L.A. County in 2000, low capacity was found in discrete Latino communities in terms of offering OSAT services in Spanish. Funding and regulation play a significant role in facilities' capacity to offer these services. Future studies should build from our multi-method approach to compare changes in population demography and system infrastructure and inform health care policy that seeks to improve providers' capacity to provide linguistically competent care.